Use of recombinant inbred strains for evaluation of intermediate phenotypes in spontaneous hypertension - Kunes, J; Kren, V; Pravenec, M; Zicha, J (Clinical and experimental pharmacology & physiology, 1994)
1. The HXB/BXH recombinant inbred (RI) strains, derived from the spontaneously hypertensive rat (SHR) and the normotensive Brown Norway (BN.1x) rat, represent a very useful system for gene mapping and for genetic analysis of certain model diseases, such as spontaneous hypertension. 2. These RI strains were genotyped in multiple genetic polymorphisms and characterized in blood pressure and some intermediate phenotypes. 3. The analysis of RI strains has revealed that (i) a gene in the vicinity of the major histocompatibility complex (RT1) on chromosome 20, a kallikrein-related gene on chromosome 4 and the renin gene on chromosome 13 were significantly associated with blood pressure, and (ii) Na+ leak in red blood cells correlated with blood pressure whereas relative heart and kidney weights as well as platelet aggregation did not.
Keywords: rekombinace genetická; Rats, Inbred BN; Rats; Animals; Phenotype; krysa rodu Rattus; Disease Models, Animal; potkani inbrední SHR; hypertenze; Rats, Inbred SHR; fenotyp; Recombination, Genetic; Hypertension; zvířata; modely nemocí na zvířatech; potkani inbrední BN